Australian trachoma surveillance annual report, 2010. - Cowling, C.; Povovic, G.; Liu, B.; Ward, J.; Snelling, Thomas; Kaldor, J.; Wilson, D. (2012)
Endemic trachoma continues to exist in remote Aboriginal communities in Australia. The National Trachoma Surveillance and Reporting Unit, established in 2006, is responsible for the collation, analysis and reporting of trachoma prevalence data and the documentation of trachoma control strategies in Australia. Data were collected from Aboriginal communities designated at-risk for endemic trachoma (defined as prevalence of 5% or greater among children) within the Northern Territory, South Australia and Western Australia. This report presents data collected in 2010. Aboriginal children aged 1-14 years were screened using the World Health Organization grading criteria to diagnose and classify individual cases of trachoma. Aboriginal adults aged 40 years or older were screened for trichiasis. Community screening coverage of the designated at-risk communities was 60% in 2010. Screening coverage of the estimated population of children aged 1-14 years and of adults aged 40 years or older in at-risk communities was 11.5% and 5%, respectively. Trachoma prevalence among children aged 1-14 years who were screened was 11%. Of the communities screened, 36% were found to have no cases of active trachoma and 55% were found to have endemic levels of trachoma. Treatment coverage of active cases and their contacts varied between jurisdictions from 64% to 90%. Trichiasis prevalence was 4% within the screened communities. This work is copyright. Apart from any use as permitted under the Copyright Act 1968, no part may be reproduced by any process without prior written permission from the Commonwealth. Requests and inquiries concerning reproduction and rights should be addressed to the Commonwealth Copyright Administration, Attorney General's Department, Robert Garran Offices, National Circuit, Barton ACT 2600 or posted at http://www.ag.gov.au/cca.